Pembelajaran IPA Dengan Model Inkuiri Terbimbing Untuk Meningkatkan Pemahaman Konsep dan Keterampilan Proses Sains Siswa SD - Munir Latukau (Peneliti.net, 2022)
This research was conducted to explore the use of guided inquiry learning models in learning natural sciences in elementary schools. The science material discussed is about simple machines. As a sample, the experimental class was chosen as a class V consisting of 40 students at one of the public elementary schools in Ternate City, North Maluku. For comparison (control) a conventional learning model was used which was also given to a class V at the same elementary school, with a total of 40 students. The experimental study focused on the effect of using the guided inquiry learning model on increasing students' understanding of science concepts and process skills. Student and teacher responses to the use of this learning model were also examined. To collect data on matters that are the focus of the research, several types of research instruments are used, namely; (1) a conceptual test in the form of an objective test, (2) a science process skills test in the form of an objective test, (3) a questionnaire to capture students' responses to the guided inquiry learning model and its use and (4) an interview format to find out the teacher's response to guided inquiry learning model. Conclusions are drawn based on the results of data processing and analysis using standard data processing and analysis techniques. The results showed that the use of the guided inquiry learning model in learning simple machine material could significantly improve students' understanding of science concepts and process skills compared to the use of conventional learning models. Teachers and most students respond positively to the use of the guided inquiry model in learning science at school. These results illustrate that the guided inquiry learning model is appropriate for use as an alternative to science learning models which besides being able to be used to improve conceptual understanding, can also be used to improve other scientific skills or skills, such as students' science process skills.